Otimização do processo de extração de compostos bioativos de folhas de jambo (Syzygium malaccense) - Savi, Aline (2015)
Red rose apple (Syzygium malaccense) is a plant cultivated in the northern and northeastern regions of Brazil, which produces a red fruit widely used in the industry as coloring and source of natural antioxidant, and used in folk medicine in curing some diseases. Studies indicate the presence of phenolic compounds and antioxidant activity in various parts of red rose apple, which generates much interest, because even provide numerous benefits to human health. To date few studies have been conducted with the leaves of rose apple, and for this reason, the study aimed to optimize the bioactive compounds extraction process. For this, there was a 23 factorial design, where the dependent variables were the total phenolic content and antioxidant activity, evaluated the kidnapping method of DPPH radical and independent variables were time, temperature and concentration of ethanol. After defined the best extraction condition, higher level time (45 min), the extract was evaluated in relation to the total phenolic content and antioxidant activity, using three different methods: kidnapping of the DPPH radical, ABTS radical capture and method reduction of iron - FRAP. The content of phenolic compounds in the extract was 73.73 ± 1.05 mg g-1 EAG. The antioxidant activity had the following values: 666,78 ± 4,61 μmol de Trolox g-1 for the kidnapping method of DPPH radical; 853,87 ± 1,47 μmol de Trolox g-1 for the kidnapping method of ABTS radical and 1267,02 ± 5,05 μmol de Fe2+ g-1 the methodology for the reduction of iron - FRAP. The results show that for some plants, the rose apple has a high content of phenolic compounds and high antioxidant activity.